Isolamento e sorologia de calicivírus e herpesvírus felino no Rio Grande do Sul e caracterização molecular dos isolados de calicivírus - Henzel, Andréia (2012)
The feline calicivirus (FCV) and the felid herpesvirus type 1 (FeHV-1) are the main agents of the respiratory tract diseases of felines. Both viruses are distributed worldwide, however its distribution and prevalence in Brazil are not well known. In the present thesis we describe the isolation and one serosurvey of FCV and FeHV-1 in some counties of the Rio Grande do Sul State, Brazil; and the molecular characterization of the capsid protein gene of FCV isolates is also described. In Chapter 1, we describe the epidemiologic survey of FCV and FeHV-1 through investigation of the conjunctival, nasal, oral and oropharyngeal swabs from 302 domestic cats. The viral isolation was performed in Crandell-Reese feline kidney cells and the isolates were submitted to PCR and RT-PCR for confirmation of the presence of the FeHV-1 and FCV, respectively. Fifty five (18.2%) of the 302 cats analyzed were positive for the viral isolation; when tested by PCR, 29 cats (52.7%) were shedding the FCV, 21 (38.2%) shedding FeHV-1, and 5 cats (9.1%) shedding both viruses. In addition, isolates of FCV and FeHV-1 were standardized to be used as control in the PCR and virus neutralization (VN) assays (serological technical used in chapter 3 of the thesis). The SV65/90 (FCV) and the SV534/00 (FeHV-1) isolates were defined as standard viruses for the assays. In Chapter 2, the molecular characterization of 13 FCV isolates is described; ten isolates came from the survey performed in chapter 1, two were deposited in the virology laboratory of the UFSM and one was obtained from a cat with gingivitis-stomatitis syndrome. The ORF2 (open reading frame) region that codifies the major protein of the viral capsid was sequenced, which includes an immunodominant region of the virus. The ORF 2 was analyzed at the nucleotide and amino acid levels and these data was used for phylogenetic studies of the 13 Brazilian isolates of FCV. These isolates were compared to ten reference strains of FCV and to the San Miguel sea lion virus type 1 (SMSV-1) as an outgroup in phylogenetic study. The primers were designed using the complete sequence of FCV-F9. The comparison of the 13 Brazilian isolates with the F9 strain revealed a large molecular diversity among them, concentrated mainly along the linear epitopes of the region. The Chapter 3 describes a serosurvey against FCV and FeHV-1 in serum samples from domestic feline. From the 630 samples tested by the VN assay, 53.6% (338/630) were positive to one or both viruses with a prevalence of 39.2% for neutralizing antibodies against FCV and 30.6% for FeHV-1. The results from the present study demonstrated that the FCV and FeHV-1 are circulating among the feline population examined, and also, the presence of carriers of the viruses among these cats. Besides, the molecular characterization of the FCV evidenced the great genetic variability of the Brazilian isolates when compared to vaccine and reference strains.